Response of eolian quartz flux and grain size in the Parece Vela Basin sediment to the mid-Pleistocene transition. (15th September 2022) - Yan, Yu; Jiang, Fuqing; Zeng, Zhigang; Zhang, Zhaohui; Zheng, Hao
Highlights: Fine-grained quartz in the Parece Vela Basin was derived from Asian interior. Mode grain size of eolian quartz responded to the strengthened westerly and Asian aridity starting from the mid-Pleistocene. Eolian quartz flux responded to Asia aridity starting from the mid-Pleistocene. Abstract: The most significant climate changes in the Quaternary occurred in the mid-Pleistocene transition (MPT). However, as the main component of eolian dust, it remains unknown how the fluxes and components of quartz responded to the MPT. We recovered a sediment core from the Parece Vela Basin (PVB), which dated back to 2.1 Ma, and quantitatively separated quartz from the sediments in order to track source area and transport mechanism. The grain size compositions, morphological characteristics, oxygen isotope compositions, and crystallinity indices of quartz showed that quartz minerals in the sediments were composed of fine-grained endmembers (EM1) with a mode grain size at 3.2 μm, and coarse-grained endmembers (EM2) with a mode grain size at 9.5 μm. The EM1 quartz mainly came from the Mongolian Gobi and Taklimakan Desert, and the EM2 quartz was predominantly derived from volcanic island arc. By fitting the grain size composition with the Weibull function, we were able to quantitatively separated EM1 and EM2 quartz fractions, and calculated the contents and mass accumulation rates (MARs) of eolian quartz. The mode grain sizes of eolian quartz increased at 1.2 Ma, but fluctuated during the mid-Pleistocene. The MARs of the eolian quartz have increased significantly since the mid-Pleistocene, most likely due to enhanced aridity in the Asia interior. Our study demonstrates that eolian quartz in the northwest Pacific can be used to trace the long-term paleoclimate change in the Asia continent.